Characteristics of a Pressurized Gas‐Solid Magnetically Fluidized Bed. Issue 2 (7th January 2013) - Zhang, J.; Feng, Z.; Jia, X.; Xu, S.; Li, W.; Du, M.
Abstract The hydrodynamic, heat and mass transfer characteristics of a pressurized co‐current gas‐solid magnetically fluidized bed (MFB) were systematically investigated considering major influence factors, such as magnetic field strength, superficial gas velocity, and operating pressure. It was shown that this pressurized gas‐solid MFB has the advantages of a wider operation range of the superficial gas velocity under bubble‐free particulate fluidization, a larger bed voidage with smaller pressure drop across the bed, and larger heat transfer efficiency, compared with a conventional fluidized bed. Moreover, the minimum bubbling velocity, gas‐solid mass, and heat transfer coefficients were correlated at high accuracy within the investigated range of operating conditions.